Potential of pharmacological and herbal for COVID-19: a narrative review - Tuba, Syahrul; Rahmania, Tesia Aisyah (Pharmacy Reports, 2021)
The pandemic coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) presents an unprecedented challenge to identify effective drugs in the prevention and treatment process. At present, there is no proven therapy for this disease, although therapeutic approaches continue to be carried out using traditional medicines (herbal) and pharmacological therapy. Information about SARS-CoV-2 virology has rapidly developed and scientists try to provide a number of potential drugs. Remdesivir has strong in vitro activity against SARS-CoV-2. Several potential drugs are currently underway in a clinical trial. Chloroquine, hydroxychloroquine, and oseltamivir have not been proven to have efficacy, and the benefits of corticosteroids are still diverse. Current clinical evidence does not support the termination of angiotensin-converting enzyme 2 (ACE2) inhibitors or angiotensin receptor blockers, coagulation therapy in patients with COVID-19 concomitant with comorbidities.